Diazotroph community structure and the role of nitrogen fixation in the nitrogen cycle in the Chukchi Sea (western Arctic Ocean). (21st May 2018) - Shiozaki, Takuhei; Fujiwara, Amane; Ijichi, Minoru; Harada, Naomi; Nishino, Shigeto; Nishi, Shinro; Nagata, Toshi; Hamasaki, Koji
Abstract: Marine nitrogen fixation occurs not only in subtropical and tropical regions but also in colder regions. However, the distribution of diazotrophs, nitrogen fixation rate, and its contribution to the nitrogen cycle in the Arctic Ocean remain poorly understood. We examined the diazotroph community structure and activity in the shelf and off‐shelf regions of the Chukchi Sea, western Arctic Ocean, during late summer 2015. The nitrate and ammonium assimilation rates were determined simultaneously to gain insights into the role of nitrogen fixation in the nitrogen cycle of the region. The diazotroph community determined by Illumina sequencing was mainly composed of Cluster III nifH phylotypes (putative anaerobes), accounting for > 80% of the total sequences examined, except for one surface sample. This result is strikingly different from previous findings in other oceanic regions. The nifH sequences other than those from Cluster III were mostly affiliated with UCYN‐A2 (symbiotic cyanobacteria), which accounted for < 15% of the total sequences. UCYN‐A2 tended to be abundant (maximum 2.9 × 10 3 copies L −1 ) in the high‐temperature low‐salinity water mass that is characteristic of Pacific‐originating water. Nitrogen fixation rate was detectable at most stations, with a range of 0.08–3.60 nmol L −1 d −1, displaying no clear relationship with depth (light intensity) or nitrate or ammonium concentration. Nitrogen fixation locally exceeded nitrate assimilation, but accounted for 1.00% at most in the total nitrogen assimilation in the euphotic zone.